(untitled) (International Journal of Engineering and Computer Science, 2018)
¾ Energy demand is expected to grow very rapidly and Distributed Generation (DG) or the alternate energy systems is expected to play an increasing role in the future of the power systems. The DG is defined as small-scale generation and can be connected at load points. DG is increasingly becoming more important in the power system because of its high efficiency, small size, low investment cost, modularity and most significantly, its ability to exploit renewable energy resources. After connecting distributed generation, part of the system may no longer be radial, which means coordination might not hold good as the traditional radial nature of the power distribution system is now converted into a multi source unbalanced network. DG may bring about reliability degradation, instead of reliability enhancement, due to relay-relay miscoordination. Current literature covers issues related with DG connection & mainly impact of DG interfacing transformer connection on IDMT over current relay. This is illustrated by test results on a system simulated using PSCAD.